Analisis Hukum Terhadap Wanprestasi pada Perjanjian Kerjasama Pengelolaan Kebun Kelapa Sawit (Studi: PT. Tepian Gayor Langkat) - Tanjung, Putri Marwin; Ramadhan, Muhammad Citra; Siregar, Fitri Dewi Yanni (JUNCTO: Jurnal Ilmiah Hukum, 2023)
The purpose of this study was to determine the implementation of the Palm Oil Plantation Management Cooperation Agreement at PT Tepian Gayor Langkat classified into default, Legal Efforts of the Parties to the act of default in the palm oil plantation management cooperation agreement at PT Tepian Gayor Langkat and Legal Consequences of Default in the Implementation of the Palm Oil Plantation Management Cooperation Agreement at PT Tepian Gayor Langkat. This research uses a normative juridical approach which is literature and field research. The results showed that the implementation of cooperation in managing oil palm plantations at PT Tepian Gayor Langkat showed that the Civil Code had accommodated well, but ended in default. Efforts were made on the act of default by giving a reprimand, a written warning, or a subpoena, making criminal law efforts by making a complaint to the North Sumatra Regional Police, and filing a lawsuit to the Medan District Court. Legal Consequences of Default in the Implementation of the Cooperation Agreement for the Management of Oil Palm Plantations at PT Tepian Gayor Langkat, namely the cancellation of the cooperation agreement and providing compensation of Rp. 200,000.00 (Two Hundred Million Rupiah).